Rancang Bangun Sistem Pengujian Performa Magneto Pesawat Cessna 172SP - Huda, Choirul; Setyawan, Herry; Nugroho, Aji Brahma; Iswahyudi, Iswahyudi (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2024)
Magneto is a component that plays an important role in the combustion performance of the Cessna 172SP aircraft engine. Component magneto maintenance is rarely carried out except when there is a failure in the combustion system, there is a 50 rpm drop difference from the two magneto which exceeds the limit magneto drop according to the reference book, a malfunction of the condenser, and a change in the timing angle on magneto which affects performance magneto cessna 172sp. The purpose of this research is to obtain the design of magneto cessna 172SP performance testing system. The research method used is to make prototype design designs that use voltage sensors, rpm sensors and temperature sensors. The faster the magnetic flux changes the greater the voltage induced in the coil. The greater the input electrical power that enters the DC motor, the greater the Rpm produced. Temperature tends to change in value due to the heat that arises in the coil due to changes in electrical energy into heat energy. It can be said that the temperature produces a constant relative value at 27°C with the value of the output voltage generated by delco. The input voltage can provide the desired rpm rotation variation, where the higher the input voltage is given, the greater the resulting output voltage will be. The relationship between the input voltage and the rpm motor rotation can provide a magnetic motor rotation torque.